Axiological entanglement of economics - Klimczak, Bożena (Annales. Etyka w Życiu Gospodarczym, 2019)
In mainstream economics, the principle of freedom from value judgment (Wertfreiheit) is enforced. This principle has different interpretations. The aim of this paper is to present the author’s interpretations of the principle of Wertfreiheit. The basic ideas of axiology have been analysed: values, valuations, and value judgments, including their application to economic activities and economic researches. Two models of valuations have been presented—the taste model and perception model—as well as points of view of economic researches on those models. The conclusion comprises the author’s interpretation of the principle of Wertfreiheit as that of impartiality and integrity in research activities.